2010
DOI: 10.1111/j.1420-9101.2010.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

Origins of cheating and loss of symbiosis in wildBradyrhizobium

Abstract: Rhizobial bacteria nodulate legume roots and fix nitrogen in exchange for photosynthates. These symbionts are infectiously acquired from the environment and in such cases selection models predict evolutionary spread of uncooperative mutants. Uncooperative rhizobia – including nonfixing and non‐nodulating strains – appear common in agriculture, yet their population biology and origins remain unknown in natural soils. Here, a phylogenetically broad sample of 62 wild‐collected rhizobial isolates was experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
223
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(246 citation statements)
references
References 98 publications
(277 reference statements)
15
223
0
1
Order By: Relevance
“…Thirdly, they may have entered the nodule as co-inoculants with other nodulating strains (Bai et al, 2003;Denton et al, 2003;Dudeja et al, 2012;Egamberdieva et al, 2010;Sturz et al, 1997). Finally they may be rhizobial strains which have lost the capacity to nodulate upon sub-culture (Howieson et al, 2000b;Sachs et al, 2010). Two non-nodulating strains (WSM4181 and WSM4182) arose from the same nodule as the effective strain WSM4186 (data not shown) which suggests that co-occupation could be a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, they may have entered the nodule as co-inoculants with other nodulating strains (Bai et al, 2003;Denton et al, 2003;Dudeja et al, 2012;Egamberdieva et al, 2010;Sturz et al, 1997). Finally they may be rhizobial strains which have lost the capacity to nodulate upon sub-culture (Howieson et al, 2000b;Sachs et al, 2010). Two non-nodulating strains (WSM4181 and WSM4182) arose from the same nodule as the effective strain WSM4186 (data not shown) which suggests that co-occupation could be a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of isolates (75) were previously assessed using greenhouse nodulation assays on A. strigosus, which has already been shown to be a permissive host on diverse Bradyrhizobium [24,43,44]. Here, we conducted greenhouse nodulation experiments on an additional 55 isolates, using identical procedures.…”
Section: Symbiotic Capacity Assessmentmentioning
confidence: 99%
“…The remaining 342 root surface isolates were classified as symbiotic or non-symbiotic based on success or failure of PCR amplification of at least one symbiosis island locus (nifD, nodD-A, nodZ, and nolL) [22,24,45]. Earlier analyses showed that successful amplification of these loci, giving a band of the correct size, is a reliable indicator of presence of the symbiosis island [24]. Many isolates were tested at two or more loci (160/342; Table S1).…”
Section: Symbiotic Capacity Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the hypothesized ecological roles of these populations remain focused on symbiosis. Similarly, previous studies have isolated Bradyrhizobium strains diminished or lacking in the ability to fix nitrogen or nodulate leguminous plants from soil, but these strains were described consistently as having transiently abandoned a symbiotic lifestyle or as relics of an ancestral symbiotic genotype (Sachs et al, 2010(Sachs et al, , 2011Okubo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%